De-centering the Myth of Normalcy in Education: A Critique of Inclusionary Policies in Education through Disability Studies - Karmiris, Maria (Critical Disability Discourses, 2017)
The intention of this paper is to inhabit a mode of exploration that foregrounds the hopeful possibility that teaching and learning might be otherwise than the continued perpetuation of hierarchies of exclusion. In focusing on this hopeful possibility, this paper focuses on two related questions. First, how does the story of normalcy continue to maintain and sustain its grip on education through inclusionary policies and practices? Second, what are the effects of this domineering narrative upon the lives of children with disabilities in our public schools? Numerous scholars in the field of disability studies with a wide array of backgrounds and research interests have offered considerable insight into how education works very hard to represent itself as a smooth road of progress and success. In part, this paper will offer a review of the literature within disability studies. The work of scholars such as Baker (2002, 2015), Nirmala Erevelles (2000, 2011, 2013) and Roger Slee (2008, 2013), who offer insights into the systemic pervasiveness of exclusionary practices in schools, will be examined as a method of exploring the tactics of the hegemonic narrative of normalcy. This paper will also offer a literature review of the work of disability studies scholars such as Annamma (2014), Hodge and Runswick-Cole (2013) and Connor (2009), who offer insights into the harm that maintaining normalcy continues to perpetuate through narratives from the perspective of disabled youth and children. In examining how hierarchies of exclusion manage to be continually reformed from the varying perspectives of these scholars, my hope is to discuss how, despite appearances to the contrary, possibilities remain for undoing the grip of normal by considering the ways in which disability studies contributes to our understanding of teaching and learning with and through differences. Keywords: inclusion, normalcy, disability, narrative, education Décentrer le mythe de la normalité dans l’éducation: Une critique des politiques d’inclusion dans l’éducation à travers les études sur le handicap Résumé L’intention de cet article est d’habiter un mode d’exploration qui met en avant la possibilité d’espoir que l’enseignement et l’apprentissage pourraient être autrement que la perpétuation des hiérarchies d’exclusion. En mettant l’accent sur cette possibilité d’espoir, ce document se concentre sur deux questions connexes. Premièrement, comment l’histoire de la normalité continue-t-elle à maintenir et à soutenir son emprise sur l’éducation à travers des politiques et des pratiques d’inclusion? Deuxièmement, quels sont les effets de ce récit dominateur sur la vie des enfants handicapés dans nos écoles publiques. De nombreux chercheurs dans le domaine des études sur le handicap avec un large éventail des milieux et d’intérêts de recherche ont offert un aperçu considérable de la façon dont le travail de chercheurs comme Baker (2002, 2015), Nirmala Erevelles (2000, 2011, 2013) et Roger Slee (2008, 2013), qui offre un aperçu de l’omniprésence systémique des pratiques d’exclusion dans les écoles, sera examiné comme une méthode d’explorer la tactique du récit hégémonique de la normalité. Cet article offrira également une revue de la littérature sur le travail des spécialistes des études sur le handicap comme Annamma (2014), Hodge et Runswick-Cole (2013) et Connor (2009), qui donnent un aperçu du mal que le maintien de la normalité continue de perpétuer du point de vue des enfants et des jeunes handicapés. En examinant comment les hiérarchies de l’exclusion peuvent être continuellement réformées à partir des perspectives variées de ces chercheurs, mon espoir est de discuter comment, malgré les apparences du contraire, des possibilités demeurent pour défaire l’emprise du normal en considérant comment les études sur le handicap contribuent à notre compréhension de l’enseignement et de l’apprentissage avec et à travers les différences. Mots clefs Inclusion; normalité; handicap; récit; éducation